MicroRNA profile analysis in the liver fibrotic tissues of chronic hepatitis B patients. Issue 2 (19th April 2017) - Chen, Rong; Wu, Jun Cheng; Liu, Ting; Qu, Ying; Lu, Lun Gen; Xu, Ming Yi
Abstract : OBJECTIVE : We aimed to identify the features of microRNA (miRNA) at different fibrotic stages in patients with hepatitis B virus (HBV)‐related liver fibrosis. METHODS : Liver tissues were collected from 40 chronic hepatitis B (CHB) patients at fibrotic stages S0–4. Microarrays of miRNAs and genomic informatics analysis were performed. RESULTS : In total, 105 miRNAs were differentially expressed in fibrotic tissues (S1–4 groups) compared with no fibrotic tissues (S0 group; P < 0.05). Combined with three classifications, 17 differential miRNAs were found to be closely related to fibrotic stages (over twofold change and P < 0.05). Five miRNAs had a signature that correlated with serum biochemical parameters and liver inflammatory grades. The receiver operating characteristic (ROC) curve showed that six miRNAs performed excellently in the diagnosis of liver fibrosis, with the area under the ROC curve (AUROC) over 0.8; among them hsa‐miR‐214‐3p had the highest AUROC (0.867). Gene ontology functions of differential miRNAs mainly involved in the cellular and developmental processes, localization, biological regulation, binding, transcriptional regulator and organelle. We also found that 23 novel signaling pathways were dysregulated in the liver fibrosis. CONCLUSIONS : MiRNA profile signature, including 17 differential miRNAs and 23 dysregulated signaling pathways, was associated with liver fibrosis. Hepatic inflammatory grades were correlated with the differential miRNA. Some miRNAs can be used for the diagnosis of liver fibrosis.